Family law and ’the great moral public interests’ in Victorian Cape Town, c.1850-1902 - Malherbe, Vertrees C. (Kronos: Southern African Histories, 2017)
In the wake of the mineral revolution, and the Cape Colony's attainment of responsible government, Cape Town's population doubled in the nineteenth century's latter years. Its largely British ruling class, seeing opportunities for wealth and a greater significance in empire and world, sought to construct a social order conducive to those goals. Faced with increasing ethnic heterogeneity, gender imbalance due to the numbers of male immigrants, and frustration in combating the endemic poverty and slums, city fathers and their closest colleagues - doctors, clergy - perceived the way forward in terms not of extending rights but of moral reform. This article carries the ongoing investigation of family life and law in Cape Town through the Victorian period. It examines legal enactments and social developments where they impacted on marriage, divorce, concubinage and related matters, with particular reference to the welfare of children and those born out of wedlock.